Subclinical Cardiac Dysfunction Is Associated With Extracardiac Organ Damages - Menet, Aymeric; Ranque, Brigitte; Diop, Ibrahima Bara; Kingue, Samuel; N'guetta, Roland; Diarra, Mamadou; Diallo, Dapa; Diop, Saliou; Diagne, Ibrahima; Sanogo, Ibrahima; Chelo, David; Wamba, Guillaume; et al. (Frontiers in Medicine, 2018)
Background: Several studies conducted in America or Europe have described major cardiac remodeling and diastolic dysfunction in patients with sickle cell disease (SCD). We aimed at assessing cardiac involvement in SCD in sub-Saharan Africa where SCD is the most prevalent. Methods: In Cameroon, Mali and Senegal, SCD patients and healthy controls of the CADRE study underwent transthoracic echocardiography if aged ≥10 years. The comparison of clinical and echocardiographic features between patients and controls, and the associations between echocardiographic features and the vascular complications of SCD were assessed. Results: 612 SCD patients (483 SS or Sβ0, 99 SC, and 19 Sβ+) and 149 controls were included. The prevalence of dyspnea and congestive heart failure was low and did not differ significantly between patients and controls. While left ventricular ejection fraction did not differ between controls and patients, left and right cardiac chambers were homogeneously more dilated and hypertrophic in patients compared to controls and systemic vascular resistances were lower (p < 0.001 for all comparisons). Three hundred and forty nine SCD patients had extra-cardiac organ damages (stroke, leg ulcer, priapism, microalbuminuria or osteonecrosis). Increased left ventricular mass index, cardiac dilatation, cardiac output, and decreased systemic vascular resistances were associated with a history of at least one SCD-related organ damage after adjustment for confounders. Conclusions: Cardiac dilatation, cardiac output, left ventricular hypertrophy, and systemic vascular resistance are associated with extracardiac SCD complications in patients from sub-Saharan Africa despite a low prevalence of clinical heart failure. The prognostic value of cardiac subclinical involvement in SCD patients deserves further studies.